2010
DOI: 10.2478/s11756-010-0099-2
|View full text |Cite
|
Sign up to set email alerts
|

A cytological observation of the fluid in the primo-nodes and vessels on the surfaces of mammalian internal organs

Abstract: Abstract:We report on the preliminary cytological observation of fluid in the primo-nodes and vessels on the surfaces of the internal organs of mammals. With some microsurgical procedures, we observed many cells and microcells that spread out of the nodes on the organ surfaces of rats and rabbits. These cells generally showed the following morphologies: (1) round or oval cells, 10 µm in size, with predominantly little cytoplasm; (2) cells with nuclei that exhibited a collapsed shape; (3) binucleated cells, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
3
1
0
1
Order By: Relevance
“…Our overall findings were similar to those of recent studies using H&E staining and electron microscopy that showed the presence of numerous immune cells in the PVS, such as MCs, macrophages, and neutrophils [1417]. We attempted to observe the PVS cells in tissue as well as the single cells in isolation from PVS tissue for more decisive observation of PVS cells.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our overall findings were similar to those of recent studies using H&E staining and electron microscopy that showed the presence of numerous immune cells in the PVS, such as MCs, macrophages, and neutrophils [1417]. We attempted to observe the PVS cells in tissue as well as the single cells in isolation from PVS tissue for more decisive observation of PVS cells.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the immune cells, such as MCs, neutrophils, eosinophils, and lymphocytes, accounted for the vast majority of the whole PVS cell population (~94%). The results strongly support that PVS may have a crucial role in the initiation and/or maintenance of immunological functions [1417]. We found the degranulation of putative MCs in the sinuses of PVs, indicating that the MCs were preferentially activated in the sinuses in PVs rather than in PNs (Figure 2(b4)).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Essential characteristic features of the primordial vascular system (endocardial circulatory system) described by Kim [1] were the thickness of the primordial vessels (endocardial vessels), the presence of the rod-shaped nuclei in a longitudinally aligned form, and the many cells in the primordial nodes (expansions), all of which are consistent with our data, as shown in figure 2a–e. The cell types inside the primordial nodes (expansions) have recently been studied morphologically [22]. In particular, the bundle-like structure observed in the distribution of the rod-shaped nuclei in figure 2e is also consistent with the claims of Kim [1].…”
Section: Discussionsupporting
confidence: 80%
“…За [6,15]. В експериментах на щурах, в умовах штучно викликаної ішемії мозку шляхом перев'язки правої загальної сонної артерії та системної гіпоксії (8% O 2 протягом 20 хв) після ін'єкції в хвостову вену стовбурових клітин, виділених з первинних судин, розмір ішемізованої тканини істотно зменшувався.…”
Section: рисунок 2 фазово-контрастне мікроскопічне зображення первинunclassified